Three new genera of oriental Xyleborina (Coleoptera: Curculionidae: Scolytinae) - Hulcr, Jiri; Cognato, Anthony I. (Zootaxa, 2009)
We describe three new genera (Ambrosiophilus gen. n., Beaverium gen. n., and Diuncus gen. n.) and diagnose 26 species of ambrosia-feeding scolytines, almost all from the Palaeotropical region. These taxa are ecologically interesting because of their intimate relationship with other xyleborine species. Recognition of these genera is an initial step towards a revision of the large polyphyletic genus, Xyleborus.